Analysis Of The Effect Of The New Advance Payment Amount On The Efficiency Of Construction Work Implementation - Muhammad Badrun Sangadji; Matitaputty, Izaac T.; Nikijuluw, Jeanee B.; Sangadji, Maryam (International Journal of Economics, Business and Innovation Research, 2025)
This research aims to analyze the influence of the down payment on the efficiency of carrying out construction work on projects managed by the Public Works and Public Housing Service (PUPR) of East Seram Regency. Down payments in construction contracts are an important factor that influences the smooth running of the project, especially in terms of time efficiency, costs and quality of work. The research method used is a quantitative approach using surveys and interviews with contractors, project supervisors and related officials. The research results show that a higher down payment can speed up project implementation in terms of time, but does not always have a positive impact on cost efficiency and work quality. Cost overruns and a decrease in quality often occur if the management of down payment funds is not properly supervised. This research provides recommendations to the PUPR Department of East Seram Regency to establish a down payment policy that is more efficient and in accordance with the characteristics of each project, as well as increasing supervision over the use of down payment funds to minimize waste and maintain the quality of construction results.